Reactive black 5 dye decolorization by heterogeneous Fenton-like reaction using Fe-clamshell catalyst / Wan Zuraida Wan Kamis and Hamizura Hassan - Hassan, Hamizura (Research Management Institute (RMI), 2012)
Fenton reaction wastewater treatment process is known to be very effective in the removal of many hazardous organic pollutants and dyestuff from water. The Fenton reaction causes dissociation of the oxidant with the formation of highly reactive hydroxyl radicals that attack and destroy the organic pollutants. However, the homogeneous Fenton process has significant disadvantages such as the generation of iron hydroxide sludge and limited range of pH. Heterogeneous Fenton is an alternative solution to overcome these limitations. Selection of catalyst support is important during the preparation of heterogeneous Fenton-like catalyst. At present, the catalyst supports include organic (such as C-Nafion and resin) and inorganic materials (such as HY zeolite, C fabrics and pillared clays). In heterogeneous solid catalyst, the iron species is "immobilized" on the solid supports or within the structure and in the pore/interlayer of the catalyst. The clam is a bi-valve mollusk of the clams family that digs in the sand. Salt-water clams are widely popular for eating purposes but the shells are considered as waste. Being inexpensive and abundant, the clam shell represents an attractive supports for iron immobilization. Therefore this study focuses on the development of heterogeneous catalysts from the low cost material, which is the clam shell. The efficiency of the heterogeneous catalyst will be tested on decolorization of model real textile wastewater that is Reactive Black 5 (RB5) by making use of a Fenton-like process. This catalyst (Fe-clamshell) will be prepared by impregnation method in which iron ion act as catalyst is attached on the supported catalyst (clamshell). The prepared catalyst is characterized by using Fourier Transform Infrared (FTIR). The effect of different reaction parameters such as different ion loading on supported catalyst, catalyst dosage, initial pH, and initial concentration of hydrogen peroxide and dye on the decolorization of RB5 will be assessed. It is expected that Fe-clamshell catalyst possess a potential to treat RB5 solution and this could give an added value since it is natural, abundant, low cost and environmentally friendly.